The Effect of Differentiated Learning on The Retainment Scores of Deep and Surface Learners - Demir, Serkan; Gurol, Mehmet (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2015)
This study aims to determine the effect of tiered instruction and station techniques of differentiated instruction on students' achievements, learning approaches and learning retainment which are important in terms of learning-teaching process. Learning approaches which was one of the variables of the research is categorized as surface and deep according to information processing preferences of students. So the effect of the differentiated instruction on students' preferences was determined to be the aim of the study. The research was applied on the 5th grade students of two elementary school using pre, post and delayed test model. Both the experiment and the control group composed of 66 students. Differentiated instructions were prepared for the course model titled Let's Learn the World of the Living of Science and Technology course. An academic achievement test which was prepared by the researcher and other professionals, was tested in terms of validity and reliability. The test was applied before, after and four weeks later than the instruction. To determine the students' approaches, Learning Approaches Inventory was applied. In terms of achievement pre-test, significant difference is detected in favor of deep learner group. According to these findings, hypothesis is proven. In terms of achievement delayed-test, significant difference is detected in favor of deep leaner group. According to these findings, hypothesis is proven.
Keywords: Differentiated learning; Tiered instruction; Station techniques; Deep learning; Surface learning; INSTRUCTION; Education & Educational Research